Development of a psychosocial-clinical nomogram to predict delayed medical help-seeking in women with stress urinary incontinence: a retrospective cohort study - Luo, Xuemei; Zhong, Yating; Ai, Dongmei; Yin, Guiqiang; Mo, Lu (Frontiers in Medicine, 2025)
BackgroundDelayed medical help-seeking is a common yet understudied behavior among women with stress urinary incontinence (SUI), potentially worsening symptom burden and diminishing quality of life. While clinical factors have been investigated, the contribution of psychosocial determinants remains poorly defined. This study aimed to identify key predictors and develop a validated nomogram for individualized risk estimation of delayed consultation.MethodsIn this retrospective cohort study, we analyzed electronic health records of 1,400 adult women diagnosed with SUI at a tertiary medical center in Southwest China (2019–2023). Delayed help-seeking was defined as > 6 months between symptom onset and first medical consultation. Multivariable logistic regression, guided by backward stepwise selection and Akaike Information Criterion, was used to identify independent predictors. A nomogram was constructed and internally validated using 1,000 bootstrap iterations. Model performance was evaluated by AUC, calibration curves, and Hosmer–Lemeshow test.ResultsDelayed help-seeking occurred in 58.0% of patients. Independent risk factors included older age (aOR = 1.03), higher BMI (aOR = 1.06), SUI duration > 12 months (aOR = 3.14), severe symptom severity (aOR = 2.06), and initial consultation with urology rather than gynecology (aOR = 1.94). Psychological predictors such as elevated anxiety scores (aOR = 1.06), perceived shame (aOR = 1.47), and social avoidance behavior (aOR = 1.66) were significantly associated with delay, while higher education was protective (aOR = 0.36). The nomogram showed strong discrimination (AUC = 0.855) and good calibration.ConclusionBoth clinical and psychosocial factors significantly influence delayed medical help-seeking in women with SUI. The proposed nomogram offers a validated, practical tool for early identification of high-risk individuals and may inform targeted interventions to reduce care delays and improve outcomes.